2011
DOI: 10.2135/cropsci2010.12.0698
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Gain in Yield and Agronomic Characteristics of Cowpea Cultivars Developed in the Sudan Savannas of Nigeria over the Past Three Decades

Abstract: A field study was conducted to determine the rate of genetic improvement in grain and fodder yields and associated agronomic and physiological changes of determinate and semideterminate cowpea [Vigna unguiculata (L.) Walp.] genotypes developed in the Nigerian Sudan savannas in 1974 to 2004. Results showed that grain yield of determinate cowpea ranged from 796 kg ha"^ for cultivars released in the 1970s to 1485 kg ha"' for cultivars released in the 2000s with a corresponding genetic gain of 2.93% per year. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Since 1970, several cowpea lines have been developed and distributed to partnership institutions in Nigeria and over 60 other countries all over the world for evaluation and release (Singh et al, 2000). Kamara et al (2011) showed genetic gain of 3.6% in grain yield of cowpea varieties developed from . Yield increases were largely associated with increased harvest index, dry matter and fodder yield.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1970, several cowpea lines have been developed and distributed to partnership institutions in Nigeria and over 60 other countries all over the world for evaluation and release (Singh et al, 2000). Kamara et al (2011) showed genetic gain of 3.6% in grain yield of cowpea varieties developed from . Yield increases were largely associated with increased harvest index, dry matter and fodder yield.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the fact that cultivars studied involved different legumes under maize of contrasting maturities with yearly variation in rainfall and temperature. Yearly variations in rainfall and temperature have been reported to provide varying environments that affect legumes (Kamara et al, 2011a). The lablab cultivars produced more pods and higher fodder yield than cowpea cultivars in all cropping systems but this did not translate to higher grain yield.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, for a given area, cowpea is likely to produce higher grain yield than lablab. The harvest index of both lablab and cowpea cultivars were low, a seeming characteristic of dual-purpose herbaceous legumes (Kamara et al, 2011a). These findings show that in crop-livestock systems, dual-purpose cowpea will furnish more grains for humans while dual-purpose lablab will provide more fodder for animals (Ewansiha et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, four varieties were early maturing, 68 medium maturing and three late maturing. According to Kamara et al (2011), most early maturing, medium maturing and late maturing cowpea varieties have determinate, semi-determinate and indeterminate growth habits, respectively. While determinate cowpea varieties are grain-type cowpea, dualpurpose cowpea is either semi-determinate or indeterminate.…”
Section: Agronomic Performancementioning
confidence: 99%